Shedding Light on NF-κB Functions in Cellular Organelles - Carrà, Giovanna; Avalle, Lidia; Seclì, Laura; Brancaccio, Mara; Morotti, Alessandro (Frontiers in Cell and Developmental Biology, 2022)
NF-κB is diffusely recognized as a transcriptional factor able to modulate the expression of various genes involved in a broad spectrum of cellular functions, including proliferation, survival and migration. NF-κB is, however, also acting outside the nucleus and beyond its ability to binds to DNA. NF-κB is indeed found to localize inside different cellular organelles, such as mitochondria, endoplasmic reticulum, Golgi and nucleoli, where it acts through different partners in mediating various biological functions. Here, we discuss the relationship linking NF-κB to the cellular organelles, and how this crosstalk between cellular organelles and NF-κB signalling may be evaluated for anticancer therapies.